Bleaching Process Investigation of Tunisian Dromedary Hair. (4th June 2013) - Harizi, T.; Dhouib, S.; Msahli, S.; Sakli, F.
Abstract : Successful bleaching of pigmented fibres was, generally, evaluated by a maximum whiteness, a minimum yellowness, and less damage to the bleached fibers. A review of the literature reveals that many studies on pigmented fibre bleaching are concerned with improving the whiteness and mechanical properties of bleached fibres. In this study, we investigate the effects of the hydrogen peroxide concentration, bleaching time, and clarification bath on the bleaching efficiency of Tunisian dromedary hair. It was showed that 30 min bleaching time gives better result in term of whiteness. However, an increased bleaching time gives an excessive damage to the bleached fibers. Further, the damage incurred by the dromedary hair was more important than that for wool, as is shown by the tenacity results. We found that oxalic acid, which is used for rinsing dromedary hair (after bleaching), provides improved results in term of whiteness obtained with bleaching. Certainly, oxalic acid made it possible to remove the maximum of iron remaining on fibre after bleaching. Bleaching methods demonstrate the excessive damage incurred by the fibre when using hydrogen peroxide particularly with raise concentration. This damage leads to adverse effects on the tenacity fibre.